PENGEMBANGAN BUKU SAKU UNTUK MENINGKATKAN PEMAHAMAN SISWA DALAM MATA PELAJARAN PAI MATERI TATA CARA SALAT KELAS II SD - Aziza, Avivatul Novi; Suyatno, Suyatno (universitas Ahmad Dahlan, 2018)
This study aims to: 1) determine the feasibility developing pocket book teaching materials on PAI subjects in class II elementary school prayer materials. 2) knowing the feasibility of PAI pocket book teaching materials for the procedure for prayer in class II of elementary school. 3) knowing the results of product trials in students' understanding through PAI pocket book teaching materials on the procedures for the elementary school class II prayer. This research is a study Research and Development (R & D). The steps are carried out, namely: (1) analysis of potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revisions, (6) product testing, and (7) product revisions, (8) usage trials. The data analysis technique used is the analysis of quantitative and qualitative data. The results of the study show that 1) the steps to develop a pocket book teaching material product include: 2) the feasibility of pocket books is done through the assessment of learning experts, material experts, linguists, and media experts. The assessment of the feasibility results from the learning expert gets a score of 75 (Good), the assessment of the material gets a score of 90 (Very good), the assessment of the linguist gets a score of 82.5 (Very Good), and the media expert gets a score of 100 (Very Good) It can be concluded that this pocket book is suitable for use. Based on product trials, it can be concluded that the pocket book material for prayer can improve student understanding as evidenced by the results of Pre Test the small group61 (Good) increasing to a value of 83 (Very Good) can be seen from the results of the Post Test. The trial of a large group of products was concluded that the book pocket material for prayer can improve students' understanding by proving that the Pre Test results scored 63.6 (Good) increased to 95 (Very Good) seen from the results of the Post Test.